RAJASTHANI CINEMA: PROBLEMS, POSSIBILITIES AND SOLUTIONS - Dadhich, Reena; Sharma, Lokesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rajasthan, a state with a rich cultural heritage and a significant film industry, has been largely overlooked in the development of regional cinema. This research paper aims to understand the history and current state of Rajasthani cinema through surveys and interviews with people associated with it. The study uses both primary and secondary data, with questionnaires and phone interviews used for data collection. The research reveals that the main problems faced by Rajasthani cinema include government ignorance, lack of constitutional recognition of the language, disinterest among the new generation, and lack of interest in Rajasthani among the audience. Other issues include financial constraints, lack of publicity, and poor scripts. The research also highlights the division of Rajasthani cinema into camps, with some actors and writers struggling to find support. The government should support Rajasthani cinema by promoting its art culture, language, and tourism to improve the situation. This could involve increasing subsidies, making locations free for cinema, arranging permission for shooting, and creating a good environment for filming. Internal reform is also necessary, with current directors and producers being encouraged to focus on creating good stories and making films available to the general public. People, artists, and technicians dedicated to Rajasthani cinema should be brought together on one platform, and interesting short films should be produced for children and youth in local languages. Increased publicity and social media use are also necessary.